Text disintegration within the academic discourse - D.A. Cheremokhina; K.K. Stebunova (Ученые записки Казанского университета: Серия Гуманитарные науки)
In line with the ideas of communicative linguistics, the text is considered as a product of discursive activity, as a means of realizing addressant’s intentions. This paper deals with the academic text, which categories and genre characteristics should correspond to the expectations of the participants of the academic discourse. It has been noted that successful academic communication arises from the compliance with the normative and communicative aspects of speech. The disagreement between the expectations of communicants entails a number of violations of a linguistic nature, which lead to the text disintegration within the academic discourse. The violations of text formation rules have been analyzed using the examples of bachelor students’ written works (essays) from the course on academic writing. Based on these examples, the signs of disintegration are illustrated: formal use of speech patterns in secondary texts, lack of their lexical and grammatical variation, inability to paraphrase the textual content in a condensed form, “isolation” from the academic communicative act. The transition to the sphere of pedagogical discourse has been identified as a key factor of disintegration, for which reason the educational goals of creating a secondary academic text are ignored. Possible solutions of the considered problem have been also provided.